KISAH KARUN DALAM AL-QUR’AN: PERSPEKTIF MAQĀṢID AL-QUR’AN YŪSUF AL-QARḌĀWĬ DALAM KAYFA NATA‘ĀMAL MA‘A AL-QUR’ĀN AL-‘AẒĬM - Halir Ridla, Moh; Fawaid, Ah (IAIN Madura, 2022)
It is profoundly noteworthy to uncover the meaning and purpose of the story in the literature scope, compared to merely recognize its figure, storyline, time and place perspective. Like the story in the Quran which occasionally has a complicated plot and is partially understood. This study aims to answer two issues, there were Karun story portrait in the Quran and the theoretical application of maqāṣid al-Qur՛ān of Yūsuf al-Qarḍawĭ in revealing the messages within Karun story. This study inferred that the Karun story in the Quran disembogued to some of the main objectives of the Quran as stated by Yūsuf al-Qarḍawĭ. There are four of seven maqāṣid al-Qur՛ān which are relevant to the Karun Story as follows: (1) the call of faith; (2) worship; (3) soul purification; and (4) guarantee of the others’ property. These four maqāṣid al-Qur՛ān are the most essential elements related faith.